Agile UX storytelling : crafting stories for better software development - Baker, Rebecca (CA Technologies, CA Press : Apress, 2017)
Learn how to use stories throughout the agile software development lifecycle. Through lessons and examples, Agile UX Storytelling demonstrates to product owners, customers, scrum masters, software developers, and designers how to craft stories to facilitate communication, identify problems and patterns, refine collaborative understanding, accelerate delivery, and communicate the business value of deliverables. Rebecca Baker applies the techniques of storytelling to all facets of the software development lifecycle--planning, requirements gathering, internal and external communication, design, and testing--and shows how to use stories to improve the delivery process. What You'll Learn: " Craft stories to facilitate communication within the project team and with stakeholders " Leverage stories to identify problems and patterns, accelerate delivery, and communicate business value " Apply storytelling techniques to all stages of the SDLC " Marshal user stories to focus requirements gathering and ensure a consistent message